In vitro Bactericidal Activities of Combination Antibiotic Therapies Against Carbapenem-Resistant Klebsiella pneumoniae With Different Carbapenemases and Sequence Types - Teo, Jocelyn Qi-Min (Frontiers Media S.A., 2022)
10.3389/fmicb.2021.779988